1999
DOI: 10.1073/pnas.96.18.10086
|View full text |Cite
|
Sign up to set email alerts
|

Horseshoe crab acetyl group-recognizing lectins involved in innate immunity are structurally related to fibrinogen

Abstract: We have characterized and cloned newly isolated lectins from hemolymph plasma of the horseshoe crab Tachypleus tridentatus, which we named tachylectins 5A and 5B (TLs-5). TLs-5 agglutinated all types of human erythrocytes and Gram-positive and Gram-negative bacteria. TLs-5 specifically recognize acetyl group-containing substances including noncarbohydrates; the acetyl group is required and is sufficient for recognition. TLs-5 enhanced the antimicrobial activity of a horseshoe crab-derived big defensin. cDNA se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
167
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 206 publications
(171 citation statements)
references
References 33 publications
2
167
0
2
Order By: Relevance
“…Interestingly, we have previously observed the formation of hexameric and octameric bouquet-like arrangements of purified TL5A by electron microscopy (7). Although TL5A crystallized with a monomer in the asymmetric unit, it is noteworthy that the crystallographic symmetry imposes a tetrameric arrangement (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we have previously observed the formation of hexameric and octameric bouquet-like arrangements of purified TL5A by electron microscopy (7). Although TL5A crystallized with a monomer in the asymmetric unit, it is noteworthy that the crystallographic symmetry imposes a tetrameric arrangement (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, TL5A exhibits strong bacterial agglutinating activity against both Gram-positive and Gram-negative bacteria. Therefore, it is likely that TL5A functions as a first-line host defense protein (7).…”
mentioning
confidence: 99%
“…For example, ficolins possess a short N-terminal collagen-like domain whereas snail FREPs have an N-terminal IgSF domain. The N-terminal regions of some FBG-bearing proteins have no homology to known proteins, for instance, horseshoe crab tachylectin [7], and most FBG-like sequences in the fruitfly Drosophila melanogaster and the mosquito Anopheles gambiae [42]. Alternatively, the molecules contain only FBG-like domain(s), as in some mosquito FBG-like sequences [42] and the slug FBG-like lectins [43].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that ascidian ficolins, the FBG-bearing proteins, bind to N-acetyl-D-glucosamine (GlcNAc) and N-acetyl-D-galactosamine (GalNAc) and activate immune responses [6]. In horseshoe crab, tachylections have antibacterial activities and also function in non-self recognition [7]. In mosquitoes of the genera Anopheles and Armigeres, FBG-like proteins have been implicated in immune responses to microbes or malaria parasites because their transcript levels are upregulated after infection [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The two proteins, however, are quite different in molecular size and amino acid sequence. Interestingly, a structural homologue of fibrinogen has recently been identified in horseshoe crab plasma, although it functions as a non-self-recognizing protein (20). The crystal structure of coagulogen suggested a possible polymerization mechanism, by which, it was theorized, the removal of the peptide C would expose a hydrophobic cove on the head of one coagulin, thereby providing a new interaction site for the hydrophobic surface of the second molecule (10).…”
Section: Discussionmentioning
confidence: 99%